Epstein–Barr virus‐specific CD8+ T lymphocytes from diffuse large B cell lymphoma patients are functionally impaired. (11th September 2015) - Cárdenas, D.; Vélez, G.; Orfao, A.; Herrera, M. V.; Solano, J.; Olaya, M.; Uribe, A. M.; Saavedra, C.; Duarte, M.; Rodríguez, M.; López, M.; Fiorentino, S.; et al.
Summary Epstein–Barr virus (EBV) is a persistent virus with oncogenic capacity that has been implicated in the development of aggressive B cell lymphomas, primarily in immunosuppressed individuals, although it can be present in immunocompetent individuals. Changes in the function and clonal diversity of T lymphocytes might be implied by viral persistence and lymphoma development. The aim of the present study was to evaluate the frequency, phenotype, function and clonotypical distribution of EBV‐specific T cells after peripheral blood stimulation with a virus lysate in newly diagnosed patients with diffuse large B cell lymphoma (DLBCL) aged more than 50 years without prior histories of clinical immunosuppression compared with healthy controls. Our results showed impaired EBV‐specific immune responses among DLBCL patients that were associated primarily with decreased numbers of central and effector memory CD8+ T lymphocytes. In contrast to healthy controls, only a minority of the patients showed CD4+/tumour necrosis factor (TNF)‐α+ T cells expressing T cell receptor (TCR)‐Vβ17 and CD8+/TNF‐α+ T cells with TCR‐Vβ5·2, Vβ9 and Vβ18 in response to EBV. Notably, the production of TNF‐α was undetectable among TCR‐Vβ5·3+, Vβ11+, Vβ12+, Vβ16+ and Vβ23+ CD8+ T cells. In addition, we observed decreased numbers of CD4+/TNF‐α+ and CD8+/TNF‐α+, CD8+/interleukin (IL)‐2+ and CD8+/TNF‐α+/IL‐2+ T lymphocytes in the absence of T cells capable of producing TNF‐α, IL‐2 and IFN‐γ after EBV stimulation simultaneously. Moreover, DLBCL patients displayed higher IL‐10 levels both under baseline conditions and after EBV stimulation. These findings were also observed in patients with positive EBV viral loads. Prospective studies including a large number of patients are needed to confirm these findings.